PENAMBAHAN ENZIIM BROMELIN UNTUK MENINGKATKAN PEMANFAATAN PROTEIN PAKAN DAN PERTUMBUHAN BENIH IKAN TAWES ( Barbonymus gonionotus) - Farah Diana; Herda Junilo Aluras; Zulfadhli Zulfadhli (JURNAL PERIKANAN TROPIS, 2017)
Bromelain enzyme is an enzyme contained in pineapple. The enzyme bromelain is a proteolytic enzyme that it has the properties hydrolyze proteins into their constituent elements. The purpose of this study is a way to improve the utilization of protein by adding the enzyme bromelain into artificial feed to increase fish growth tawes. This study have using an experimental method and these was conducted from March 2016 to May 2016 at the Hatchery of Teuku Umar Teuku Umar, West Aceh district using completely randomized design with 4 treatments and 3 replications. Treatment of dose of the enzyme bromelain is differences, namely P0 with doses of 0%, P1 with a dose of 2%, with a dose of 4% P2 and P3 with a dose of 6%. Test fish are given feed ad libitum or until full. The results showed that the enzyme bromelain with different doses have not significantly affect the efficiency of feed utilization and survival. While enzyme bromelain with different doses have significantly affect to protein efficiency ratio, growth rate and the growth rate of biomass show. Value range of protein efficiency ratio is ±1,86-2.26%, value range of the growth rate is ± 2.16 - 2.64% and the rate of growth of the biomass is ± 0.019 to 0.117 grams. The quality of water, i.e. temperature is 26o-30oC and pH value is 7.7-8.4.